Enhancing transmission and distribution system coordination and control in GB using power services from DERs. Issue 18 (4th June 2019) - Martínez Sanz, Inmaculada; Stojkovska, Biljana; Wilks, Angela; Horne, Jonathan; Ahmadi, Ali R.; Ustinova, Tatiana
Abstract : This study describes the technical principles behind the Power Potential innovation project in Great Britain (GB). The project aims to enable distributed energy resources (DERs) connected to the distribution network to provide services to the transmission grid, in a coordinated manner. This study focuses on the dynamic voltage control and the provision of reactive services that can be exercised through these assets. The specific control principles to enable participation of different DER technologies (synchronously and non‐synchronously connected) to provide transmission support are described here. Simulation studies are included to theoretically validate the proposed solution using a detailed dynamic model of the transmission–distribution network in GB. The value of this control approach as a new tool for the system operator is also highlighted and the next steps for the Power Potential project are finally summarised.